Three-Dimensional CT for Quantification of Longitudinal Lung and Pneumonia Variations in COVID-19 Patients - Chen, Qiuying; Chen, Lv; Liu, Shuyi; Chen, Luyan; Li, Minmin; Chen, Zhuozhi; You, Jingjing; Zhang, Bin; Zhang, Shuixing (Frontiers in Medicine, 2021)
Objectives: Visual chest CT is subjective with large inter- and intra-observer variability. We aimed to quantify the dynamic changes of lung and pneumonia on three dimensional CT (3D-CT) images in coronavirus disease 2019 (COVID-19) patients during hospitalization. Methods: A total of 110 laboratory-confirmed COVID-19 patients who underwent chest CT from January 3 to February 29, 2020, were retrospectively reviewed. Pneumonia lesions were classified as four stages: early, progressive, peak, and absorption stages on chest CT. A computer-aided diagnostic (CAD) system calculated total lung volume (TLV), percentage of low attenuation areas (LAA%), volume of pneumonia, volume of ground-glass opacities (GGO), volume of consolidation plus GGO: consolidation ratio. CT score was visually assessed by radiologists. Comparisons of lung and pneumonia parameters among the four stages were performed by one-way ANONA with post hoc tests. The relationship between CT score and volume of pneumonia, and between LAA% and volume of pneumonia in four stages was assessed by Spearman’s rank correlation analysis. Results: The patients underwent a total of 534 chest CT scans with a median interval of 4 days (interquartile range, 3-5 days). TLV, LAA% and GGO: consolidation ratio were significantly decreased while volume of pneumonia, GGO, and consolidation were significantly increased in the progressive and peak stages (for all, P<0.001). CT score was significantly correlated with the pneumonia volume in the four stages (r = 0.731, 0.761, 0.715, and 0.669, respectively, P<0.001). Conclusion: 3D-CT could be used as a useful quantification method in monitoring the dynamic changes of COVID-19 pneumonia.